Staging the ‘Forgotten Genocide’ in the Aftermath of the Dirty War: Una bestia en la luna by Richard Kalinoski - Strichartz, Ariel (Latin American Theatre Review, 2015)
The most recent Argentine military dictatorship (1976-1983) and the Armenian Genocide (1915-1923) share legacies of state-sanctioned denial and impunity, which have left survivors and subsequent generations grappling with issues of memory and mourning. The intersection of these two collective memories in Argentina, home to a sizable Armenian population, offers a glimpse into how post-dictatorial and post-genocidal memory politics have borrowed from and shaped each other. This article examines the positive reception in Argentina of Una bestia en la luna by the U.S. playwright Richard Kalinoski. While the work treats the struggles of two survivors of the Armenian Genocide and sets its dramatic action in the U.S., Kalinoski’s use of photography to warn against the dangers of silencing memory engages non-Armenian spectators in postdictatorial Argentina.